Diocesan Bishop and Temporal Goods of the Church - I Made Markus Suma (P3TK, Sanata Dharma University, 2018)
To govern his diocese, a diocesan Bishop exercises the threefold power of governance, namely legislative, executive and judicial power. As regards the executive power he can exercise personally or through another person. Administrative power becomes the area for the exercise of the executive power, including in the administration of temporal goods of the diocese and of other public juridical persons subject to him. In performing a good administration of the temporal goods of the Church, a diocesan Bishop needs to comply with pertinent canonical norms as well as to collaborate with respective council or persons concerned to avoid the abuse of power or misuse of temporal goods. The matter in question is discussed in the view of canonical analysis. This research aims at obtaining canonical assessments to the authority of diocesan Bishop in administering Churchs properties according to their proper purposes.